Editor’s Note - González-Crespo, Rubén (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The research works presented in this issue are based on various topics of interest, among wich are included: Mobile services, gesture recognition, physics simulation, management decision support, business intelligence, Internet, remote executables, scientific computing, university-industry links, Sony AIBO, Aperios, toolchain, MAS, data fusion, tracks, merge, inference, Homeland Security, european projects, research trends, emerging technologies and desk research.
Keywords: Editors Note; IJIMAI